Transformasi Ekonomi Lokal melalui Pengolahan Singkong dalam Tinjauan Ekonomi Syariah Sebagai Upaya Peningkatan Kesejahteraan Masyarakat - Teguh Ansori (Musyarakah: Journal of Sharia Economic (MJSE), 2025)
This study aims to analyze the empowerment of cassava farmers in Dayakan Village, Badegan District, Ponorogo Regency through the Asset Based Community Development (ABCD) approach in the perspective of Islamic economics. Before the program, farmers faced low cassava prices, limited market access, and weak bargaining power against middlemen. These conditions resulted in unstable farmer incomes and stagnant welfare. Through the initiative of processing cassava into value-added products, such as steamed cassavacake and various other local food products, farmers incomes increased significantly and their bargaining position in the market became stronger. Analysis using the maqasid al-syariah framework shows that this empowerment supports the preservation of wealth (hifz al-mal), life (hifz al-nafs), intellect (hifz al-aql), progeny (hifz al-nasl), and religion (hifz al-din). In addition, community participation through the principles of musyarakah and syura demonstrates the practice of economic justice, social cohesion, and the value of taawun (mutual assistance). This empowerment also emphasizes sustainability in the economic, social, and environmental dimensions, which is in line with the principle of istimar al-ard (prosperity of the earth) and the prohibition of israf (wastefulness). The results of the study confirm that empowerment based on local potential is not only capable of improving the welfare and income of rural communities, but also serves as a tangible implementation of Islamic economics oriented towards justice, benefit, and long-term sustainability. These findings provide practical contributions to the development of rural economies as well as strengthening the theory of locally-based Islamic economics.